Information System for Industrial Mapping at the Industrial Department in Samarinda City - Ladrika Eka Putri; Asep Nurhuda; Fajar Ramadhani (TEPIAN, 2022)
The progress and development of increasing data demand human progress to become someone more advanced. So that everything related to data and information will be more structured and transparent if it is carried out and processed using information technology, including in government agencies. The Department of Industry of Samarinda City always collects data. the existence of industry in the city of Samarinda every year experiences data development and changes. The obstacle is that every industrial data collection was done manually and the officers finding the location of the industry had to contact the village office while not all industries were recorded in the village data. This study uses data collection methods, namely interview and observation methods. The result of this research is an industrial mapping information system at the Industrial Office of Samarinda City based on Android that can be used to help officers find out the distribution of industrial location points in Samarinda City and make it easier for users to find out industrial location routes.